Advantages and Disadvantages of Medical Abortion, According to Brazilian Residents in Obstetrics and Gynaecology - Bento, Silvana Ferreira; Pádua, Karla Simônia de; Pacagnella, Rodolfo de Carvalho; Fernandes, Karayna Gil; Osis, Maria José Duarte; Duarte, Graciana Alves; Faúndes, Anibal (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To find out which was the opinion of residents in obstetrics and gynecology about the advantages and disadvantages of medical abortion as compared with surgical procedures.Method Cross-sectional multicenter study among residents in obstetrics and gynecology from 21 maternity hospitals located in 4 different geographical regions of Brazil, using a self-responded questionnaire with 31 questions related to their opinion and experience on providing abortion services.Results Most residents agreed that “being less invasive” (94.7%), “does not require anesthesia” (89.7%), “can be accompanied during the process” (89.1%), “prevents physical trauma” (84.4%) were the main advantages of medical abortion.Conclusion Residents perceived both clinical and personal issues as advantages of medical abortion.
Keywords: abortion; legal abortion; hospital medical staff; brazil